The Metaphorical Thinking of Junior High School Students in Solving Algebra Problems - Julia Noviani (Edumatika : Jurnal Riset Pendidikan Matematika, 2022)
Metaphorical thinking is one way of thinking in building abstract concepts through concrete things. Abstract ideas in metaphorical thinking are metaphorized into real-world things. This study aims to describe the metaphorical thinking profile of junior high school students in solving algebraic problems. The problem-solving steps used are the Polya model and the stages of metaphorical thinking using the CREATE criteria by Siler. This research is qualitative research using a descriptive approach. This study involved one of the seventh-grade students in a private junior high school in Surabaya who got the highest score on the preliminary test, namely the mathematical ability test. The data collecting technique employed in this study was problem-solving assignments and semi-structured interviews. Time triangulation was performed to assess the data from this study's credibility. Based on the analysis results, the subject has not been optimal in revealing the CREATE criteria for metaphorical thinking. The research subject has not been able to find a suitable metaphor for the algebra problem, so the subject did not reveal the Connect and Relate criteria. However, the subject revealed Explore criteria by designing mathematical models on the algebraic problem. The subject was able to determine the mathematical processes needed to solve the problem for the Analyze criteria, and the subject was also able to explain the procedures she took before. The subject discovered the Transform criteria by inferring and interpreting data based on earlier work. Last, the subject revealed the Experience criteria by explaining a new challenge using the model that had been created previously.